Pentingnya Apologetika menurut 1 Petrus 3:15-16 bagi Penginjilan - Antonio, Lucky (Sekolah Tinggi Teologia Kerusso Indonesia, 2021)
Apologetics as a branch of Theology is based on the main purpose that is to bring people to maturity and spread the Gospel. Reading the Bible in a holistic way, apologetics has been executed since the very beginning of the world’s existance and apologetics was started by God Himself when He answered those who opposed Him. Appologetics has continued to the first church and up to now when proofing the truth of the Christian belief during evangelisation and even as an act of counselling. The connection between apologetics and evangelisation is quite close, as apologetics try to answer the questionings of the Chritian beliefs,which could be a direct act of evangelisation. Wilbur Smit wrote “a spoken or written accountability of what we are doing or the Truth we are believing”. Wilbur Smit believes that being accountable is part of our conviction. Very fundamental as an apologetic is that he should have a deep conviction and sanctifies Christ in his life. This is a key factor, because the presuppostion here is that the Jesus Christ is Lord of the thoughts of an apologetic. The apologetic arguments should be towards the Lordship of Jesus Christ and wisdom of God and founded on the fear of the Lord. Foolishnes of unbelief is not to be exposed for apologetic is as neutral as other human activity. Any apologetic argument should have the Truth of God as the presupposition.